Aflatoxins in foodstuffs: current concepts on mechanisms of toxicity and its involvement in the etiology of hepatocellular carcinoma - Oliveira, Carlos Augusto Fernandes de; Germano, Pedro Manuel Leal (Revista de Saúde Pública, 1997)
Current concepts derived from intensive research over the last decade, on biotransformation, mechanisms of toxicity and evidences for the involvement of aflatoxins in the etiolgy of human liver cancer are summarily presented. Aflatoxin B1(AFB1), the main metabolite produced by moulds of genus Aspergillus, exerts its effects after conversion to the reactive compound AFB1-epoxide, by the action of cytochrome P450-dependent enzymes. This epoxide can form derivatives with cellular macromolecules, including proteins, RNA and DNA. The reaction with DNA occurs with guanines in the códon 249 of tumor suppressor gene p53. Primary biotransformation of AFB1 also produces hydroxylated and less toxic derivatives, such as aflatoxins Q1 and P1. Differences intra and interspecies in the pathways of activation/detoxification are directly related to the susceptibility of animals to aflatoxin effects. In humans, studies of individual biomonitoring of AFB1 metabolites such as AFB1-N7-guanine have demonstrated that aflatoxins constitute an important risk factor for hepatocellular carcinoma (HCC) in exposed populations. Some of these studies also show a synergistic action between aflatoxins and the hepatitis B virus in the development of human HCC. In view of these concepts, and taking into account the frequent detection of aflatoxins in Brazilian foodstuffs, the need for investigation into the level of exposure to these toxins and its impact on human health is stressed.